The new avant-garde : issues for the Art of the Seventies - Müller, Grégoire (London : Pall Mall Press London, 1972)
Andre, Carl ; Beuys, Joseph ; Flavin, Dan ; Heizer, Michael ; LeWitt, Sol ; de Maria, Walter ; Merz, Mario ; Morris, Robert ; Nauman, Bruce ; Serra, Richard ; Smithson, Robert ; Sonnier, Keith
Engels
kunstcatalogus